Collections of the Natural History Museum of Lille: VIII-Diplostraca (types and figured specimens) - Hennion, Marie (2015)
The Diplostraca (also known as conchostracans; Arthropoda: Crustacea: Branchiopoda: Phyllopoda) are a group that were often collected in the coal basins of northern and eastern France, during the main period of activity of the coal industry (end of 19th Century to beginning of 20th Century); others were collected in Germany, Switzerland, Africa and Russia. Hence, the palaeontological collections of Lille (Natural History Museum of Lille and University of Lille) are especially rich in specimens. This paper presents a reasoned catalogue of the types and figured specimens of the collection of the Natural History Museum of Lille, associated with a brief review of the Palaeozoic diplostracans, and some new or updated data in geology and palaeontology. Fossil Diplostraca are a rather neglected group, which appears however to be important in biostratigraphy, sequential stratigraphy, palaeoclimatology, palaeobiology, palaeoecology and palaeobiogeography during both principal stages of the Late Carboniferous (Pennsylvanian); i.e., during Moscovian (traditionally called Westphalian in western Europe) and Kasimovian times (traditionally called Stephanian).